Molecular Testing for Targeted Therapy in Advanced Non–Small Cell Lung Cancer: Suitability of Endobronchial Ultrasound Transbronchial Needle Aspiration. Issue 4 (1st October 2015) - Casadio, Chiara; Guarize, Juliana; Donghi, Stefano; Di Tonno, Clementina; Fumagalli, Caterina; Vacirca, Davide; Dell'Orto, Patrizia; De Marinis, Filippo; Spaggiari, Lorenzo; Viale, Giuseppe; Barberis, Massimo
Abstract: Objectives: Endobronchial ultrasound-guided transbronchial needle aspiration (EBUS-TBNA) is a minimally invasive procedure that has revolutionized the diagnosis and staging of lung cancer. The goal of the present study was to investigate the yield and applicability of molecular testing in the specimens obtained by EBUS-TBNA from patients with advanced non–small cell lung cancer (NSCLC), comparing the results with a series of patients who underwent diagnostic surgical procedures in the same institution. Methods: The study followed 306 consecutive patients with clinically diagnosed primary lung cancer who had the EBUS-TBNA procedure. EGFR and KRAS mutations were evaluated on cytologic specimens by Sanger sequencing and Cobas real-time polymerase chain reaction, whereas ALK rearrangement was tested by fluorescence in situ hybridization. The results were compared with those obtained from a series of 1, 000 NSCLC surgical samples routinely analyzed. Results: Molecular testing was possible in 96.9% of the samples obtained by EBUS-TBNA. EGFR (exons 18–21) mutations were found in 16.9%, KRAS mutation (exons 2–3) in 31.6%, and ALK rearrangement in 3.9% of the cases. In the surgical series, the mutations' distribution were 14.8%, 29.0%, and 3.4%, respectively. There were no statistical differences between the two series . Conclusions: Our study demonstrates that EBUS-TBNA can be effectively used not just for diagnosis but also for complete mutational testing.